High efficiency AlGaInP-based 660-680nm vertical-cavity surface emitting lasers - Figiel, J. J., author; Kilcoyne, S. P., author; Lear, Kevin L., author; Choquette, K. D., author; Schneider, R. P., author; Crawford, M. Hagerott, author; IEE, publisher (Colorado State University. Libraries, 1995)
Record continuous-wave output power of 2.9mW and 10% peak wallplug efficiency have been achieved from planar gain guided AlGaInP-based vertical-cavity surface emitting lasers. These results represent nearly an order of magnitude improvement in performance over previous AlGaInP-based vertical-cavity lasers.
Keywords: visible semiconductor lasers; vertical cavity surface emitting lasers